ICE CORES FROM SVALBARD - USEFUL ARCHIVES OF PAST CLIMATE AND POLLUTION HISTORY - Isaksson E.; Hermanson M.; Hicks S.; Igarashi M.; Kamiyama K.; Motoyama H.; Watanabe O.; Moore J.; Muir D.; Pohjola V.; Vaikmäe R.; van de Wal R.S.W. (My University, 2003)
Ice cores from the relatively low-lying ice caps in Svalbard have not been widely exploited in climatic and environmental studies due to uncertainties about the effect of melt water percolation. However, results from two recent Svalbard ice cores, at Lomonosovfonna (1250 m asl) and Austfonna (750 m asl), have shown that with careful site selection, high-resolution sampling and multiple chemical analyses, it is possible to recover ice cores with partly preserved annual signals. These cores are estimated to cover at least the past 600 years and have been dated using a combination of known reference horizons and glacial modeling. The δ18O data from both Lomonosovfonna and Austfonna ice cores suggest that the 20th century was the warmest during the past 600 years. A comparison of the ice core and sea ice records from this period suggests that sea ice extent and Austfonna δ18O are linked over the past 400 years. This may reflect the position of the storm tracks and their direct influence on the relatively low altitude Austfonna. Lomonosovfonna may be less sensitive to such changes and primarily record atmospheric changes due to its higher elevation. The anthropogenic influence on Svalbard environment is illustrated by increased levels of non-sea-salt sulphate, nitrate, acidity, fly-ash and organic contaminants particularly during the second half of 1900s. Decreased concentrations of some components in recent decades most likely reflect emission and use restrictions. However, some current-use organic pesticide compounds show growing concentrations in near surface layers.
Keywords: Ice core chemistry; Climate variability; Organic contaminants; Pollen; Svalbard